Cenário da produção animal no Estado do Pará a partir do censo agropecuário do IBGE de 2017 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
With the aim of providing important information about the livestock sector in the State of Pará, this study carried out a statistical survey by integration region with the aim of pointing out, through the variables analyzed, the main limiting factors for livestock production in Pará. Based on data from the 2017 IBGE Agricultural Census, the data were grouped according to the 12 integration regions of the State of Pará (Araguaia, Baixo Amazonas, Carajás, Guamá, Lake Tucuruí, Marajó, Metropolitana de Belém, Rio Caeté, Rio Capim, Tapajós, Tocantins and Xingu) for subsequent comparative analysis. The variables analyzed were: origin of the technical guidance received, area groups, producer's condition in relation to the land, typology, control of diseases and/or parasites, food supplementation and processing. Descriptive statistical analysis of the data was carried out using sectoral graphs prepared in Microsoft Excel software. In the State of Pará, it was observed that 87% of rural producers own the establishments analyzed, access to rural technical assistance (ATER) is limited to 6% of the number of establishments, and the origin of this service is offered in approximately 50% by government agencies and 29% comes from the producer himself. parasites.
Keywords: Produção pecuária; Sistemas de produção; Zootecnia; CNPQ:: CIÊNCIAS AGRÁRIAS